PENGARUH MODEL PEMBELAJARAN JOYFULL LEARNING BERBANTUAN MEDIA DOX-CARD PADA MATERI POKOK REDOKS - Astrian, Dewi; Hadisputro, Subiyanto; Nurhayati, Sri (Chemistry in Education, 2013)
This study aims to find out the influence of Joyfull Learning model assisted by dox-card medium to the chemistry learning result in the subject matter of redox in class X SMAN 1 Tengaran of academic 2011/2012. This study population is the whole X classes in SMAN 1 Tengaran of academic year 2011/2012. Samples in this study were drawn with cluster random sampling technique; the samples obtained were the X-8 class as the experimental class given Joyfull Learning model assisted by chemo-edutainment dox-card medium and X-7 class as the control class given conventional model. Based on the research results, it obtains post test average score of experimental class of 83.12 and of control class in the amount of 76.18. The post test score of experimental class and control class have normal distribution and equal variants, whereas in the t test of the right party, the tcount is (2.05) > ttable (1.18) which means that the average score of the experimental class is better than the control class. The hypothesis testing using biserial correlation coefficient and determination coefficient. Based on the research results. It can be concluded that there is an influence of Joyfull Learning models assisted by dox-card medium to the students’ score of class X SMAN 1 Tengaran in redox subject matter, as indicated by the correlation coefficient () of 0.51 with 26,04% influence.